Does work-life balance have a relationship with work performance? - Norzita, S.; Arabi, Arrominy; Zurraini, Arabi; Jati Kasuma, Ali; Norlelawati, I.; Yusman, Yacob (MASMED UiTM Shah Alam, 2020)
Attaining work-life balance is challenging. Juggling work and personal affairs can be a highly demanding effort and the inability to attend to everything can leave one frustrated and exhausted. Increased level of stress, turnover and absenteeism rate are some of the negative repercussions of this. This study therefore, aims to further examine the relationship between work-life balance and work performance among non-executive level staff at Sarawak State Civil service. There were 44 acceptable self-administered questionnaires collected and analysed out of 64 questionnaires that were distributed for this exploratory stage of study. The result disclosed a significant but weak relationship between work-life balance and job performance. As the result, the study proposes to outline a work-life balance practices or programs such as job design that helps in employee productivity, employee assistance programs, health programs, aerobic sessions, family day and encouragement for employees to participate in seminars on stress and time management. Genuine concern and extensive involvement of the company in achieving the work-life balance will yield positive outcome from the employees.